INFLUENCE OF EMOTIONAL INTELLIGENCE ON CAREER READINESS OF MANAGEMENT STUDENTS IN CHANDRAPUR DISTRICT - Shukla, Megha K; Hingane, Kavita B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With the tide of the fast evolving employment environment in the 21st century, academic excellence is not the only factor that graduates need to excel in, emotional intelligence (EI) has proved to be an important skill that affects the employment preparedness of graduates. The study described in this research paper reviews the role of emotional intelligence on the career readiness of management students in Chandrapur district of Maharashtra. The paper explores the level to which the building blocks of EI related to self-awareness, self-regulation, motivation, empathy, and social skills can lead to promoting employability and ability to adapt in the workplace of future managers. A sample of final-year management students of a number of institutes in the district formed the secondary data that was directly taken by using a structured questionnaire on the Likert scale. The research utilizes descriptive and inferential statistics in deriving the results of the data and obtains the extent and form of the association between emotional intelligence and career readiness. In its findings, there is a significant positive correlation between higher emotional intelligence and a higher readiness in careers particularly, in such areas as team work, leadership talent, decision making and ability to deal with stress. Statistical disparity in levels of EI and career preparedness against gender and the institution background is also mentioned in the study. In the related study, it is emphasized that emotional intelligence should also be included in curricular structures especially in management studies, in order to prepare students better to handle the demands of their professional life. It is suggested that the industry-specific soft skills trainings and EI modules can be put in place to close the gap between the academic curriculum and the professional requirements.